Perception and enterprise communication networks to improve the requirements elicitation process - Luzuriaga, Juan Manuel (2002)
The requirements elicitation phase of software development projects is characterised by the intensity and importance of communication activities. Requirements elicitation is a traditional exploratory phase in which context is analysed and an abstraction is performed as a consequence. However, exploratory processes are characterised by a deep interaction with environmental factors. In this paper, we present a process for managing communication during the requirements elicitation phase. Our process would help get well-defined requirements by using knowledge inside organisations and a classification of requirements perception based on how environment is controlled by stakeholders. Our approach can be used to guide the elicitation process as well as to validate the requirements.